Особливості адаптації систем радіоакустичного зондування атмосфери до змін навколишнього середовища - Карташов, О. В. (ХНУРЕ, 2025)
The analysis of known methods of frequency adaptation of radioacoustic atmospheric sounding (RAS) systems to environmental changes is performed. The synthesis of an effective algorithm for adapting RAS systems to variable external atmospheric conditions is considered, obtained using the basic principles of the theory of stochastic optimal control and the theory of measuring radio systems. A new structure of the system for adapting and controlling the parameters of the sensing system is proposed. It is shown that the use of linear sequential filtering algorithms allows to significantly reduce random errors of measurement results and significantly reduce the impact of dynamic errors on the efficiency of controlling the frequency of the sensing signal by fulfilling the Bragg condition.
Keywords: радіоакустичне зондування атмосфери; зміни навколишнього середовища